Bridging science and heritage in the Balkans - Balkan Symposium on Archaeometry (Oxford)
vi, 155 sayfa
Keywords: “In a period when, particularly in the West, the study of archaeological remains is enriched through new methods derived from the natural sciences and when there is general agreement on the need for more investment in the study, restoration and conservation of the tangible cultural heritage, this book presents contributions to these fields from South-Eastern Europe. This region is characterised by a contrast between the rather limited development of the above scientific methods and the particularly rich and diverse material remains of its past societies, as well as by an obvious need to bring closer together traditionally-trained archaeologists with specialists in natural sciences interested in the research and conservation of ancient material remains. The title ‘Bridging Science and Heritage in the Balkans’ intends to show that the volume is part of this effort. The departing point of this volume is the 5th Balkan Symposium of Archaeometry (25–29 September 2016, Sinaia, Romania), where most of the papers published here were presented in preliminary form. The contributors are specialists from South-Eastern Europe as well as from other European countries working there. Some chapters focus on methods (in the research of glass, restoration of stone monuments affected by contemporary graffiti, conservation by irradiation of organic materials such as wood and human and animal body remains); most chapters present case studies (analyses of ceramics, metals, soils, wood anatomy, isotope-based reconstruction of human diet, ancient DNA, radiocarbon dating, technology assisted field survey, as well as restoration of paper and pigments); sometimes several methods are combined. The volume covers nearly all aspects of heritage sciences employed in this part of Europe“ --